Charged black holes in Einsteinian cubic gravity and nonuniqueness - Rocha, J. V.; Antonia M. Frassino (23rd International Conference on General Relativity and Gravitation, 2022)
A well-appreciated perk of general relativity is that its vacuum black hole solutions are uniquely determined by their mass and angular momentum. Upon the inclusion of a minimally coupled Maxwell field, this uniqueness theorem extends to electrovacuum black holes, in which case one more parameter is needed to specify the solution: charge. The proof of the theorem relies heavily on the structure of the Einstein equations and therefore it is expected to be evaded in modified gravity. This is shown to be the case for Einsteinian cubic gravity, a modification of general relativity that includes up to third-order curvature corrections determined by low-energy effective theory expectations. Specifically, and restricting to spherically symmetric four-dimensional geometries, we find that there exist two black holes with the same mass and charge in a certain overextremal regime (i.e., charge greater than the mass). Both solutions are pathology-free, asymptotically flat, and none of them features a Cauchy horizon, in contrast with the usual Reissner-Nordstrom spacetime. A brief discussion of these solutions’ thermodynamic properties is also presented. Finally, it is pointed out that neutral black holes in Einsteinian cubic gravity coexist with a one-parameter family of naked singularity spacetimes carrying the same mass.